Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 9362 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Pandionidae", "Country is Mexico" ] } The dataset includes 9362 records from 54 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002429-150831095807960/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences